2005
DOI: 10.1093/ajcn/82.2.471
|View full text |Cite
|
Sign up to set email alerts
|

A combination of prebiotic short- and long-chain inulin-type fructans enhances calcium absorption and bone mineralization in young adolescents

Abstract: Daily consumption of a combination of prebiotic short- and long-chain inulin-type fructans significantly increases calcium absorption and enhances bone mineralization during pubertal growth. Effects of dietary factors on calcium absorption may be modulated by genetic factors, including specific vitamin D receptor gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
215
2
24

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(260 citation statements)
references
References 19 publications
10
215
2
24
Order By: Relevance
“…59 A previous study demonstrated that a mixture of short-and long-chain inulin-type fructans, given as prebiotics during adolescence as oral supplements for a 1-year period, increases bone mineralization and calcium absorption. 60 A possible explanation of the effect of dietary or prebiotic fiber on bone metabolism is the effect of the fiber on calcium absorption; the microbiota ferments the fiber to short-chain fatty acids (SCFAs), reducing the gut pH, thus reducing the formation of calcium phosphates and increasing the calcium absorption favoring bone. In the studies on the effect of prebiotics calcium absorption was investigated, whereas immune phenotype and inflammation were not.…”
Section: Gut Microbiota Immune System and Bonementioning
confidence: 99%
“…59 A previous study demonstrated that a mixture of short-and long-chain inulin-type fructans, given as prebiotics during adolescence as oral supplements for a 1-year period, increases bone mineralization and calcium absorption. 60 A possible explanation of the effect of dietary or prebiotic fiber on bone metabolism is the effect of the fiber on calcium absorption; the microbiota ferments the fiber to short-chain fatty acids (SCFAs), reducing the gut pH, thus reducing the formation of calcium phosphates and increasing the calcium absorption favoring bone. In the studies on the effect of prebiotics calcium absorption was investigated, whereas immune phenotype and inflammation were not.…”
Section: Gut Microbiota Immune System and Bonementioning
confidence: 99%
“…Of course, a concomitant trend towards an increase in mineral bioavailability and oestrogen mimetic effect cannot be ruled out (Scholtz-Ahrens et al 2001). Indeed, according to the data published by Abrams et al (2005), a mixture of chicory long-chain inulin and oligofructose is able to increase calcium absorption in volunteers and to impact markers of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos foram desenvolvidos em países europeus (Holanda 10,11 e França 12 ) e nos Estados Unidos da América [13][14][15][16] , com os protocolos experimentais aprovados pelos Comitês de Ética em Pesquisa das respectivas instituições. Os participantes e/ou seus responsáveis legais foram esclarecidos a respeito dos objetivos e procedimentos adotados e consentiram em participar dos estudos.…”
Section: R E S U L T a D O Sunclassified
“…11 avaliaram somente meninos, Griffin et al 13,14 recrutaram apenas meninas pré-púberes e púberes (com idade próxima à primeira menarca), e Abrams et al 15 selecionaram meninos e meninas pré-púberes.…”
Section: Caracterização Dos Indivíduos E Cálculo Do Tamanho Da Amostraunclassified
See 1 more Smart Citation